2002
DOI: 10.1128/cdli.9.2.236-242.2002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in CD4 + , CD8 + , CD4 + CD8 + , and Immunoglobulin M-Positive Peripheral Blood Mononuclear Cells of Postweaning Multisystemic Wasting Syndrome-Affected Pigs and Age-Matched Uninfected Wasted and Healthy Pigs Correlate with Lesions and Porcine Circovirus Type 2 Load in Lymphoid Tissues

Abstract: Forty-one 8-to 12-week-old wasted pigs were selected from several conventional farms with histories of postweaning multisystemic wasting syndrome (PMWS) and classified into two groups according to their porcine circovirus type 2 (PCV2) infection status, as determined by in situ hybridization (ISH). Twenty-four pigs tested positive for PCV2 (PCV2-positive group), while 17 pigs tested negative for PCV2 (PCV2-negative group). In addition, eight uninfected healthy pigs from an experimental farm were used as contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 23 publications
8
56
0
1
Order By: Relevance
“…Our results suggest that the ORF4-deficient PCV2 is involved in virulence and replication in vivo. We also found that the relative proportions of CD4 ϩ , CD8 ϩ , and CD4 ϩ CD8 ϩ T cells were downregulated in PCV2⌬-and wPCV2-infected mice, similar to previous findings for PCV2-infected pigs (52). Furthermore, compared to wPCV2-infected mice, the mutant virus exhibited a greater decrease of CD4 ϩ and CD8 ϩ T cells in infected mice (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Our results suggest that the ORF4-deficient PCV2 is involved in virulence and replication in vivo. We also found that the relative proportions of CD4 ϩ , CD8 ϩ , and CD4 ϩ CD8 ϩ T cells were downregulated in PCV2⌬-and wPCV2-infected mice, similar to previous findings for PCV2-infected pigs (52). Furthermore, compared to wPCV2-infected mice, the mutant virus exhibited a greater decrease of CD4 ϩ and CD8 ϩ T cells in infected mice (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…PCV2 can induced a lymphopenia, involving an early loss of B lymphocytes, concomitant with depletion of helper (both naive and memory/ activated), cytotoxic, and ␥␦ T cells, as well as natural killer cells (37). Despite these observations, virus antigen has not been clearly demonstrated in lymphocytes (11,42,45,47). It has been reported that virus impairment of DC function can have consequences on T-lymphocyte survival and anergy (23).…”
mentioning
confidence: 87%
“…Em condições experimentais, o período de incubação pode chegar a 2-4 semanas (Allan et al 1999a, Balash et al 1999, Harms et al 2001, período no qual o acúmulo de vírus necessário para iniciar a doença é alcançado. Quanto maior a quantidade de antígeno vírico detectada, maior a depleção linfóide , Darwich et al 2002, Chianini et al 2003, Darwich et al 2003.…”
Section: Resul II Resul Ii Resul Ii Resul Ii Results T T T Tadunclassified